China is Poorer than we Thought, But No Less Successful in the Fight Against Poverty - Chen, Shaohua (World Bank, Washington, DC, 2012)
In 2005, China participated for the first time in the International Comparison Program (ICP), which collects primary data across countries on the prices for an internationally comparable list of goods and services. This paper examines the implications of the new Purchasing Power Parity (PPP) rate (derived by the ICP) for China's poverty rate (by international standards) and how it has changed over time. We provide estimates with and without adjustment for a likely sampling bias in the ICP data. Using an international poverty line of USD 1.25 at 2005 PPP, we find a substantially higher poverty rate for China than past estimates, with about 15% of the population living in consumption poverty, implying about 130 million more poor by this standard. The income poverty rate in 2005 is 10%, implying about 65 million more people living in poverty. However, the new ICP data suggest an even larger reduction in the number of poor since 1981.